Operations management : Processes and Supply Chains - Lee J. Krajewski (Pearson Education Limited, 2015)
This fully revised new edition provides a comprehensive introduction to the wide-ranging subject of Operations Management. The book is clearly written and jargon-free, concentrating on examining the ways an organisation turns its resources into goods or services. The student-centred approach based on learning objectives, case studies activities and review questions is ideal for those studying the subject, whilst its practical approach provides help to managers seeking to become more effective.